Judicial Review of the Constitutional Court Decision Number 93/PUU-XX/2022 on Guardianship for Persons with Mental Disabilities from a Human Rights Perspective - Febriyanti, Riska; Antasari, Rr Rina; Afriansyah, Syafran (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
This article is motivated by the Constitutional Court Decision Number 93/PUU-XX/2022 concerning the judicial review of Article 433 of the Indonesian Civil Code, particularly the phrases “dungu” (feebleminded), “sakit otak” (mentally ill), and “mata gelap” (dark-minded). The Court held that these terms are no longer relevant in light of modern scientific developments and may perpetuate discriminatory stigma against persons with disabilities; however, they were nevertheless retained within the legal norms. The central problem of this study is to examine the judicial considerations in Decision Number 93/PUU-XX/2022 and its juridical review from a human rights perspective.This study employs a normative juridical method with a statutory approach and a case approach. The findings reveal that although the Court acknowledged that the terms are scientifically outdated, the phrases were still maintained. From the principle of equality before the law, the decision raises critical concerns as it potentially perpetuates stigma and is inconsistent with Article 28D paragraph (1) of the 1945 Constitution as well as the Convention on the Rights of Persons with Disabilities (CRPD). From the Islamic perspective, the ruling is also incompatible with the objectives of maqasid al-shariah, particularly the principle of hifz al-nafs (protection of life). Therefore, reform of legal terminology toward more humane and inclusive language is urgently required so that the law truly reflects substantive justice and guarantees equality for every citizen. [Artikel ini dilatarbelakangi oleh Putusan Mahkamah Konstitusi Nomor 93/PUU-XX/2022 terkait pengujian Pasal 433 KUHPerdata, khususnya frasa “dungu”, “sakit otak”, dan “mata gelap”. Mahkamah menyatakan bahwa istilah-istilah tersebut tidak relevan dalam perkembangan ilmu pengetahuan modern serta berpotensi menimbulkan stigma diskriminatif terhadap penyandang disabilitas, namun tetap mempertahankannya dalam norma hukum. Permasalahan utama penelitian ini adalah bagaimana pertimbangan hakim dalam Putusan Nomor 93/PUU-XX/2022 serta bagaimana tinjauan yuridisnya ditinjau dari perspektif hak asasi manusia.Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan dan pendekatan kasus. Hasil penelitian menunjukkan bahwa meskipun Mahkamah menilai istilah tersebut tidak lagi relevan secara ilmiah, frasa tersebut tetap dipertahankan. Dari sudut pandang asas equality before the law, putusan ini menimbulkan catatan penting karena berpotensi melanggengkan stigma serta tidak sejalan dengan Pasal 28D ayat (1) UUD 1945 dan Konvensi Hak-Hak Penyandang Disabilitas (CRPD). Dalam perspektif Islam, hal ini juga tidak sejalan dengan maqasid al-shariah, khususnya prinsip hifz al-nafs atau perlindungan jiwa. Oleh karena itu, pembaruan terminologi hukum yang lebih manusiawi dan inklusif sangat diperlukan agar hukum benar-benar mencerminkan keadilan substantif serta menjamin kesetaraan bagi setiap warga negara..]